A Study on Knowledge Related to Oral Cancer and Attitude towards Screening among Patients Attending a Rural Hospital in West Bengal - Arpan Kumar Ghorui; Bobby Paul; Lina Bandyopadhyay; Madhumita Bhattacharyya; Ankush Banerjee; Niladri Sekhar Pal (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Oral cancer is a major public health problem in India. Screening of the disease has an important role in early detection resulting in improved patient outcomeswith reduced mortality and morbidity. The present study was undertaken to assess the awareness about oral cancer and attitude towards screening among patientsattending a rural hospital in West Bengal and elicit its associated factors if any. Method: This cross-sectional study was conducted from September to December 2020 among 244 adults attending the Dental OPD ofAmtala Rural Hospital, South 24 Parganas, West Bengal. Data collection was done via face-to-face interview using a pre-tested structured questionnaire.Knowledge regarding oral cancer and attitude towards screening was assessed using an 18-itemand 8-item questionnaire respectively. Logistic regression analysis was done to find out the factors associated with satisfactory knowledge and favourable attitude. Results: Satisfactory knowledge of oral cancer was observed among 26.6%, while favourable attitude towards screening among 29.9% of the participants. Younger age,educational level above secondary and non-usage of smokeless tobacco were significantly associated with satisfactory knowledge of the disease. Educational level above secondary, nuclear family membersand smokers hada significant association with favourable attitude towards screening. Conclusion:There was a lack of awareness about oral cancer and an unfavourable attitude towards screening among a significant proportion of the participants. Intensive health education for increasing community-level awareness about the disease and benefits of routine screening would help in the reduction of the burden of oral cancer in the future.